KUALITAS PELAYANAN DI KECAMATAN GUBENG KOTA SURABAYA - Putra, Ady Kusuma (JPAP: Jurnal Penelitian Administrasi Publik, 2018)
Since the era of reform in Indonesia, the role of government in realizing good governance especially in terms of service delivery to the public through the improvement of the performance of the state apparatus has become one of the steps taken to perfect the bureaucratic order, leading to the process of bureaucratic reform. Even since formulated Law no. 23 of 2014 on local governments directed to be able to provide an innovation in the provision and improvement of service quality. The formulation of the problem in the lift in the performance study of service quality in sub-district gubeng surabaya city. The method used in this research is the method of quality analysis of data management techniques in the form of a description of words, from interviews or observations in the field then analyzed in order to get a conclusion. Based on the authors observation about the performance of service quality in sub-district gubeng surabaya more improve the service quality which is considered less satisfactory in the service process that is the dimension of physical facility (tangible) so that society can feel satisfied and comfortable while carry out service in Sub Gubeng. In order for the continuity of service to run smoothly, should be considered again facilities and infrastructure in the office, such as parking space in the extension, seats for the community, waiting for the service process should be adequate and feasible to use. Keywords: Performance, quality of public service